2018
DOI: 10.1002/app5.230
|View full text |Cite
|
Sign up to set email alerts
|

Aid Policy and Australian Public Opinion

Abstract: Since 2013, Australian aid has been reduced and increasingly focused on delivering benefits to Australia. Motivated by these changes, this paper fills three gaps in the existing literature on public opinion about aid. It provides the only recent detailed study of Australians' opinions about aid. It studies specific policy questions in addition to the broader questions typical of international research. And it studies views on the purpose of aid, an area not previously researched. Although Australians are gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Moreover, a substantial body of work in behavioral economics, psychology and political science has provided evidence that people behave altruistically in certain circumstances (Ahlquist and Levi 2013;Gintis et al 2003). Also, some observational studies of views on aid purpose have also found majorities of respondents believe aid should be focused primarily on helping other countries (Wood 2018a).…”
Section: Changing Public Opinion About Aidmentioning
confidence: 99%
“…Moreover, a substantial body of work in behavioral economics, psychology and political science has provided evidence that people behave altruistically in certain circumstances (Ahlquist and Levi 2013;Gintis et al 2003). Also, some observational studies of views on aid purpose have also found majorities of respondents believe aid should be focused primarily on helping other countries (Wood 2018a).…”
Section: Changing Public Opinion About Aidmentioning
confidence: 99%
“…For example, Corbett's ( 2017 ) history of the Australian aid program consistently highlights the crucial role of executive discretion, while Wells ( 2019 ) highlights how the highly centralised budget process in Australia, operating through the Expenditure Review Committee of Cabinet, further propels the centralisation of decision‐making around aid volumes. None of this is to deny the role of public opinion in shaping Australian aid policy (for an overview of how, see Wood, 2018 ). Indeed, the interview data we report below shows that Australian politicians are acutely aware of how aid issues are perceived by their constituents.…”
Section: Before Covid‐19: Three Eras Of Australian Aidmentioning
confidence: 99%
“…Whereas the goal of poverty reduction proved to be one of partisan disagreement during the period of the Abbott government, the threat of Chinese influence is a concern shared across parliamentarians from both major parties. More broadly, this suggests that the left‐right divide that Wood ( 2018 ) describes in public opinion on Australia's foreign aid, may recede into the future in the context of the perception of threat posed by China.…”
Section: During Covid‐19: Elite Perspectives On How the Pandemic Will Impact Australian Aidmentioning
confidence: 99%
See 2 more Smart Citations